Uji Kadar Kafein dan Uji Organoleptik Terhadap Pembuatan Teh Daun Kopi Robusta - Rahayu, Ranti; Effendi, Darwan; Sari, Venti Novita (Jurnal Agroteknologi (Agronu), 2025)
Pruned coffee leaves are often regarded as waste, thus requiring further utilization. This study aimed to determine the caffeine content and organoleptic characteristics (color, aroma, and taste) of coffee leaves through the appropriate roasting duration in the production of tea from robusta coffee leaves. The research was conducted from January to March 2025 in two locations: Tanjung Dalam Village and the Laboratory of the University of Bengkulu. A quantitative analysis method was used, followed by an organoleptic test on four sample treatments: P0 (no roasting), P1 (roasting for 30 minutes), P2 (roasting for 40 minutes), and P3 (roasting for 50 minutes) at a temperature of 40°C. The results showed that the highest caffeine content was found in sample P0 (1.82%), followed by P2 (1.71%), P1 (1.62%), and P3 (1.44%). Meanwhile, the organoleptic test revealed that the most preferred tea by the panelists was P3 (roasting for 50 minutes at 40°C), with an average score of 11.94.